Tyrants Writing Poetry - Kaminskij, Konstantin; Koschorke, Albrecht, 1958- (Book collections on Project MUSE., 2017)
Why do tyrants - of all people - often have poetic aspirations? Where do terror and prose meet? This book contains nine case studies that compare the cultural history of totalitarian regimes. The essays focus not on the arts, literature or architecture but on the phenomenon that many of history's great despots considered themselves talented writers. By studying the artistic ambitions of Nero, Mussolini, Stalin, Hitler, Mao Zedong, Kim Il-sung, Gaddafi, Saddam Hussein, Saparmurat Niyazov and Radovan Karadzic, the authors explore the complicated relationship between poetry and political violence.